The concise Corsini encyclopedia of psychology and behavioral science (John Wiley & Sons, 2004)
Edited by high caliber experts, and contributed to by quality researchers and practitioners in psychology and related fields. Includes over 500 topical entries Each entry features suggested readings and extensive cross-referencing Accessible to students and general readers Edited by two outstanding scholars and clinicians